Optimal Coastal Gate Operation Method through Simulation-Optimization Approach - Pakorn Ditthakit; Suwatana Chittaladakorn (Agriculture and Natural Resources, 2008)
Coastal gate refers to the water gate constructed in a coastal river basin. Initially, the main purpose of construction of this water control structure is to prevent saline water intrusion into upstream freshwater and also storage freshwater along the water by closing the water gates during the dry season. Nevertheless, the water gate cannot be permanently closed due to the requirement of environmental flow which provides the critical contributions to river health, economic development and poverty alleviation. Therefore, it is necessary to develop a methodology for appropriately operating the coastal gate, which corresponds to various objectives of water resources management system simultaneously. In this paper, the methodology for planning optimal coastal gate opening serving several desired state variables through simulation-optimization approach is presented. The Differential Evolution (DE) approach and River Operation Model (ROM) are applied herein as the optimization and simulation model, respectively. The developed method was then applied to the problem of coastal gate operations in Pak Phanang River Basin (PPRB), which mainly covers the area in Nakhon Si Thammarat province, the southern part of Thailand. The results illustrated that the purposed model can be used as decision support model for management of optimal coastal gate operations under several environmental, ecological and hydraulic conditions.